2007
DOI: 10.1073/pnas.0706404104
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the incretin-bound extracellular domain of a G protein-coupled receptor

Abstract: Incretins, endogenous polypeptide hormones released in response to food intake, potentiate insulin secretion from pancreatic ␤ cells after oral glucose ingestion (the incretin effect). This response is signaled by the two peptide hormones glucose-dependent insulinotropic polypeptide (GIP) (also known as gastric inhibitory polypeptide) and glucagon-like peptide 1 through binding and activation of their cognate class 2 G protein-coupled receptors (GPCRs). Because the incretin effect is lost or significantly redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

21
286
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(308 citation statements)
references
References 60 publications
21
286
0
1
Order By: Relevance
“…This is consistent with the results of an Ala scanning analysis described by Dean et al [31] and of the recently published crystal structure of a PTH (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) peptide in complex with the PTH1R ectodomain [12]. Here, we extend these investigations by testing the whole PTH ligand for interactions.…”
Section: Accepted M Manuscriptsupporting
confidence: 91%
“…This is consistent with the results of an Ala scanning analysis described by Dean et al [31] and of the recently published crystal structure of a PTH (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) peptide in complex with the PTH1R ectodomain [12]. Here, we extend these investigations by testing the whole PTH ligand for interactions.…”
Section: Accepted M Manuscriptsupporting
confidence: 91%
“…However, these efforts have been hampered by technical difficulties in purifying soluble and functional proteins in the large quantities required for structural studies. Very recently, the structures of the receptor ECD-ligand complexes have been reported for the murine CRF receptor 2␤ (CRFR2␤) and the human GIPR (37,38). These structures reveal a similar scaffold of two antiparallel ␤-sheets, resembling a short consensus repeat (SCR) fold found in immunoglobins (37,38).…”
mentioning
confidence: 99%
“…Although a number of structure−activity relationships studies on VIP have been reported, 28,29 our design rationale was based on the hypothesis that VIP binds the VPAC 2 receptor in an α-helical conformation, in an analogous manner to that demonstrated for GIP binding the extracellular domain of its receptor. 30 28 ). With the latter null residues in mind, we felt that functionalization in these positions would retain both the active structure and original potency/selectivity profile, while shielding potentially susceptible protease cleavage sites.…”
mentioning
confidence: 99%
“…We then transposed M 17 to I 17 , facilitating synthesis and purification of the native peptide, a well tolerated modification, which has been exploited in half-life extension strategies. 32 Incorporation of a C-terminal extension motif G 29 K 30 provided not only a potential reactive handle, but also acts to neutralize the macrodipole and offers helix-capping hydrogen bonds, based on the structure of receptor-bound GIP (Figure 1). Table 1 shows that the initial modifications made to wildtype VIP did not compromise functional VPAC 2 agonism, and therefore, I 17 -VIP-GK serves as a good reference peptide against which other analogues described here may be compared.…”
mentioning
confidence: 99%